The Role of Grass vs. Exogenous Abrasives in the Paleodietary Patterns of North American Ungulates - Semprebon, Gina M.; Rivals, Florent; Janis, Christine M. (Frontiers in Ecology and Evolution, 2019)
The attainment of high crowned teeth (hypsodonty) has often been thought to be associated with grazing because many abrasive opal particles are known in grass that are presumed to wear down mammalian teeth. Equids have often been discussed regarding tooth morphological change due to the evolution of highly hypsodont teeth over time, the hyper-grazing habits of modern horses, and the originally-held view that the acquisition of hypsodonty and the widespread appearance of grasslands were synchronous. Recent studies, however, have reported asynchrony in the origin of hypsodonty and the widespread appearance of grasslands and have considered exposure to exogenous grit as important evolutionary drivers of hypsodonty in ungulates. We tracked changes in crown height (hypsodonty index), relative abrasion (mesowear) and food and grit scar topography on dental enamel (microwear) to examine the relative contributions of grass versus grit as a driving force in ungulate tooth changes during the evolution of North American Equidae compared to four North American ruminant artiodactyl families (Camelidae, Antilocapridae, Dromomerycidae, and Merycoidodontidae). We found that the overall pattern of the timing of the attainment of hypsodonty is inconsistent with grazing as the main impetus for the “Great Transition” within equids nor within the artiodactyl families as highly hypsodont ungulates post-date the spread of widespread grasslands. Mesowear closely mirrored hypsodonty trends in all families. Microwear patterns, particularly high degrees of enamel pitting (particularly large pits) and unusually coarse scratch textures in all five families, are consistent with exposure to exogenous grit as the main driver of hypsodonty acquisition prior to the consumption of significant levels of grass. Equidae exhibited a wider array of dietary behavior than the other families through most of their evolutionary history. Even so, grass was a much more common dietary item for equids than for the other families, and when combined with exogenous grit, which was more accelerated from the early Miocene onward based on more pitting and coarser scratch textures, may explain the more extreme acquisition of hypsodonty in equids compared to the artiodactyl families studied and set the stage for the Equidae alone to become hypergrazers in the Recent.